Three Limitations of Algorithmic Reason: Steering the Human Mind in the Twenty First Century - Castro, P. (2022)
Artificial Intelligence has pervaded contemporary societies in almost every way as an externalized, fragmented, and optimized form of rationality. I call this externalized mode of thought “algorithmic rationality” and to the ideology favoring it, “algorithmic reason”. Although algorithmic reason original goal was to facilitate the arising of a highly participative and global Culture, fitting all citizens in a dynamic democratic society, History has it that AI technology would be ceased by consumer logic and computational propaganda. I discuss the economical, epistemological, and political implementation of algorithmic reason, introducing three cases. I argue that such implementation comprises a cybernetic loop, involving a centralized AI and its instrumentalized users. Commenting upon the ubiquity of such loop, I introduce three limitations of algorithmic reason. The first two are of a computational nature. The third owes its presence to a cybernetic loop, producing a steering effect on the human mind and promoting a cultural flattening effect. This, I conclude, may result in the impoverish of creativity, critical thought, and intellectual curiosity.